Reliability-Based Post-Quantum Digital Signature on Multi-Parametric Groups - Khivrenko, H. O. (ХНУРЕ, 2025)
This paper addresses reliability and safety assurance for computer and information systems threatened by future quantum adversaries [5]. We outline a digital signature scheme over non-commutative multi-parametric groups (NMPGs) whose hardness relies on simultaneous conjugacy/decomposition problems rather than integer or lattice structures. The design is reliability-first: deterministic signing (to avoid RNG induced failures), constant-time word- reduction kernels, explicit verification equations with localizable failure, and built-in assurance artifacts (known-answer tests, power-on self-tests, duplication checks, and fault handling aligned with FMEA). Parameter agility enables uplift without key-format churn, supporting long-lived deployments. While complementary to NIST-standardized PQC (and therefore useful for crypto-diversity), the proposal emphasizes engineering properties important in safety-critical contexts: predictable worst-case execution time, side-channel resilience practices, and evidence-friendly testing for certification.
Keywords: post-quantum cryptography; non-commutative groups; digital signatures; reliability engineering